Association Between Methylmalonic Acid and Cognition: A Systematic Review and Meta-Analysis - Wang, Chao; Zhang, Ying; Shu, Jianbo; Gu, Chunyu; Yu, Yuping; Liu, Wei (Frontiers in Pediatrics, 2022)
Background：Methylmalonic acid (MMA) is an intermediate metabolite of human body. The content of MMA in the blood of healthy people is very low, and its concentration will increase in some diseases and elderly people. Recent studies have shown that MMA has a variety of biological functions. The correlation between MMA and cognition, one of the important functions of the nervous system, is still uncertain. Objective：Meta-analyses were performed to assess whether elevated MMA was associated with the risk of cognitive decline. Methods：Cross-sectional studies, randomized controlled studies, and case-control studies on the relationship between MMA and cognition were obtained by searching PubMed, Web of Science, EMBASE, ProQuest, WANFANG MED ONLINE, China National Knowledge Infrastructure (CNKI) and Chongqing VIP until May 2022. Two researchers independently selected studies according to inclusion and exclusion criteria, evaluated study quality and extracted data. Meta-analyses were performed using Review Manager 5.4 software. The sensitivity analysis of meta-analysis was performed by One by one exclusion method. Results：A total of 11 studies were included, including 6 cross-sectional studies, 2 randomized controlled studies and 3 case-control studies, with a sample of 16,533 subjects. Meta-analysis showed that there was no significant difference in cognitive level between high-level MMA subjects and low-level MMA subjects in the general population (SMD = -2.19, 95% CI (- 4.76 ~ 0.38), Z = 1.67, P = 0.09); In the population supplemented with VitB12, the increase of MMA level caused by VitB12 supplementation was not related to the change of cognition (SMD = 0.32, 95% CI (- 0.19 ~ 0.84) z = 1.22, P = 0.22); There was also no significant difference in MMA levels between patients with dementia and the control group (WMD = 20.89, 95% CI (- 5.13 ~ 46.92), z = 1.57, P = 0.12). Conclusions：In the general population, whether VitB12 is supplemented or not, there is no correlation between the increase of MMA level and the decrease of cognitive level. In dementia diseases, the level of MMA did not change significantly. High levels of MMA may not be a risk factor for cognitive impairment. The exact relationship between MMA and cognition needs further research.